Do preferences for urban amenities differ by skill? - Arntz, Melanie; Brüll, Eduard; Lipowski, Cäcilia (Journal of Economic Geography, 2023)
By investing in urban amenities, city-level policies often aim to attract highly skilled workers. However, studies relying on revealed preferences struggle to provide causal evidence that skilled workers value urban amenities more than less skilled workers. Therefore, we use a stated-preference experiment with hypothetical job choices between two cities that differ in wages, urban amenities and economic dynamism. We find that respondents are willing to forgo a significant fraction of their wages for better urban amenities. Most strikingly, preferences do not differ systematically by skill level. Hence, the higher fraction of highly skilled workers in amenity-rich places stems from the inability of low-skilled workers to move to and afford living in their preferred locations.
CRIS-Team Scopus Importer:2025-02-03
Keywords: C99; choice experiment; R23; R58; regional policy; skill selective migration; Urban amenities

The minimum wage in the roofing sector: impact on employment, worker protection and competition Der Mindestlohn im Dachdeckerhandwerk: Auswirkungen auf Beschäftigung, Arbeitnehmerschutz und Wettbewerb - Aretz, Bodo; Arntz, Melanie; Gregory, Terry; Rammer, Christian (Journal for Labour Market Research, 2012)
The Minimum wage in the roofing sector, which was introduced in 1997 and transferred to a national and generally binding level in 2003, has particularly affected the sector in Eastern Germany, even in an international comparison. However, the concomitant effective cost burden is limited. Based on difference-in-differences estimations in comparison to an ancillary construction sector that is not affected by minimum wages as well as based on a comparison of workers in the roofing sector who have been affected by minimum wage introduction to different degrees, causal effects with regard to employment, worker protection and competition are investigated. The results show that the wage increases associated with the minimum wage introduction only partially compile into earnings increases. Moreover, the overall employment situation does not seem to change even though some negative employment results can be detected for workers affected by binding minimum wages. This might be due to the fact that, at least partially, cost increases caused by minimum wage introduction are transferred to the customers by increasing prices. Distinct effects on the competitive situation cannot be shown; however, there is a certain shift in the East German start-up activity and corporate structure toward single-person companies.
CRIS-Team Scopus Importer:2025-02-03

The Sorting of Female Careers after First Birth: A Competing Risks Analysis of Maternity Leave Duration - Arntz, Melanie; Dlugosz, Stephan; Wilke, Ralf A. (Oxford Bulletin of Economics and Statistics, 2017)
A number of contributions have found evidence that motherhood is a critical life event for women's employment careers. This study presents a detailed analysis for the duration of maternity leave in which young mothers can make a transition into different types of employment, unemployment as well as the next birth. We provide a comprehensive picture of the sorting mechanisms that lead to the differentiation of women's employment careers after birth. Our empirical evidence is derived from large-linked administrative individual labour market data from Germany for a period of three decades. We obtain unprecedented insights into how women's skills, the quality of the previous job match, firm level characteristics, labour market conditions and leave legislation are related to the length of maternity duration. Expansionary leave policies, e.g. are found to be a key factor for the rising share of women who have their second child out of inactivity.
CRIS-Team Scopus Importer:2025-02-03
Keywords: erwerbstätige Frauen; Mütter; Berufsverlauf; Erwerbsunterbrechung; Elternzeit; Erziehungsurlaub; Berufsrückkehr; institutionelle Faktoren; Familienpolitik; IAB-Biografiedaten; Vollzeitarbeit; Teilzeitarbeit; Arbeitsplatzwechsel; Dauer; Bundesrepublik Deutschland

Working from Home and COVID-19: The Chances and Risks for Gender Gaps - Arntz, Melanie; Ben Yahmed, Sarra; Berlingieri, Francesco (Inter economics, 2020)
As the COVID-19 pandemic causes a record number of people to work from home, this disruptive event will likely have a long-lasting impact on work arrangements. Given existing research on the effects of working from home on hours worked and wages, an increased availability of working from home may provide a chance for women to catch up with their male counterparts. Yet, the need to simultaneously care for children during the COVID-19 lockdown may also revive traditional gender roles, potentially counteracting such gains. We discuss the likely effects of the COVID-19 pandemic on gender gaps in the labour market and at home in light of recent empirical findings and novel statistics on the heterogeneous structure of work arrangements among couples. We construct a novel teleworkability index that differentiates between fully teleworkable, partly teleworkable and on-site jobs and find that in about a third of households the COVID-19 shock is likely to induce shifts in the intra-household allocation of tasks from mothers to fathers.
CRIS-Team Scopus Importer:2025-02-03
Keywords: Pandemie; Auswirkungen; Telearbeit; geschlechtsspezifische Faktoren; Mütter; erwerbstätige Frauen; Beruf und Familie; Gleichstellung; Geschlechterverhältnis; BIBB/BAuA-Erhebung; Arbeitsplatzpotenzial; Kinderbetreuung; Arbeitsteilung; Bundesrepublik Deutschland